Detoxification of mycotoxin patulin by the yeast Rhodosporidium paludigenum. (15th July 2015) - Zhu, Ruiyu; Feussner, Kirstin; Wu, Tao; Yan, Fujie; Karlovsky, Petr; Zheng, Xiaodong
Highlights: Yeast Rhodosporidium paludigenum degrade patulin by intracellular enzyme. The enzyme responsible for patulin degradation is inducible by patulin. Patulin-degrading enzyme does not require dissociable cofactors. The degradation product is desoxypatulinic acid as indicated by UPLC–MS. The product is less toxic to Arabidopsis, E. coli and human liver cells. Abstract: Patulin is a mycotoxin produced by Penicillium species which often contaminates fruit and fruit-derived products. In this work the degradation of patulin by the yeast Rhodosporidium paludigenum was studied and the toxicity of the degradation product was determined. Patulin-degrading activity of R. paludigenum was inducible by patulin; it was located within yeast cells and the enzyme did not require a dissociable cofactor. Chromatographic behavior and molecular mass of the degradation product indicated that R. paludigenum transformed patulin into desoxypatulinic acid. The degradation product was significantly less toxic to Arabidopsis thaliana and human liver cells than patulin; it was not toxic to Escherichia coli at the highest concentration tested. The detoxification activity of R. paludigenum toward patulin is a promising tool for the control of patulin contamination in food and feed.